One theoretical framework for understanding current LGBT issues in Serbia today - Antonić, Slobodan (Sociološki pregled, 2021)
The first part of the article describes the ideological disputes in the Serbian public related to the proposal for the adoption of three laws: on same-sex marital union, on gender equality and on the prohibition of gender discrimination. The second part of the article proposes a modified version of the theory of the world capitalist system and neocolonialism as a theoretical framework for explaining these political and ideological controversies. In conclusion, the author states that it is certainly possible to contextualize these ideological and political disputes theoretically in a different manner, but that the proposed theoretical framework enables a coherent understanding of other dominant social phenomena in Serbia.